Generation Z : a century in the making - Seemiller, Corey; Grace, Meghan (Routledge, Taylor and Francis Group, 2019)
No other generation in history has received as much coverage as the Millennial generation. Books, Google searches, blogs, and news articles are everywhere about them. Yet, Generation Z is comprised of our youth and young adults today and has received very little attention comparatively. Those in Generation Z are among our youngest consumers, students, colleagues, constituents, voters, and neighbors. Being able to better understand who they are and how they see the world can be helpful in effectively working with, teaching, supervising, and leading them. Generation Z: A Century in the Making offers insight into nearly every aspect of the lives of those in Generation Z, including a focus on their career aspirations, religious beliefs and practices, entertainment and hobbies, social concerns, relationships with friends and family, health and wellness, money management, civic engagement, communication styles, political ideologies, technology use, and educational preferences. Drawing from an unprecedented number of studies with higher education research institutions, market research firms such as Pew and Census, other generational researchers and industry leaders, this is the authoritative defining work on Generation Z that market researchers, consumer behaviour specialists, and employers sorely need - and it is a fascinating read for anyone interested in the sociology of generations.- Resumé vydavatel
Keywords: generace Z; mezigenerační vztahy; generation Z; intergenerational relations; elektronické knihy; monografie; electronic books; monographs